PENEGAKAN HUKUM PERATURAN WALIKOTA PEKANBARU NOMOR 39 TAHUN 2014 TENTANG KAWASAN TANPA ROKOK - Muklis Al` Anam; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Law enforcement is a means of realizing the law aspired by the law maker. The creation of legal certainty and related to justice. Law enforcement is related to the provision of sanctions to violators of legal products, both administratively, civilly, and criminally. In Pekanbaru Mayor Regulation Number 39 of 2014 about Non-Smoking Areas Article 19 paragraph (1), which contains administrative sanctions such as; written warnings, suspension of activities, and revocation of permits. This type of research is empirical juridical research or sociological legal research, a research approach that emphasizes the legal aspects about the subject matter to be discussed, associated with the reality in the field. This research was conducted at the Pekanbaru City Government Office, Pekanbaru City Regional House of Representatives, Pekanbaru City Health Office, and Pekanbaru City Civil Service Police Unit. The sample population is the whole related to the research problem. Sources of data used are primary data and secondary data, data collection techniques in this study is by observation, questionnaires, interviews and literature review. In the results of research problems there are three main things that can be concluded. First, the 2014 Pekanbaru Mayor's Regulation No. 39 on non-smoking areas has not yet been implemented. Two obstacles to the implementation of these regulations are the local regulation/regional head regulation, human resources and consistency of law enforcement officers. The three future efforts of Pekanbaru City Government in cigarette advertising are through sponsorship, print media, and job advertisements (Job advertisements) and public service advertisements (PLA).Keywords: Law Enforcement, No Smoking Area, Pekanbaru City